Protective effects of Poria cocos and its components against cisplatin-induced intestinal injury. (6th April 2021) - Zou, Ye-Ting; Zhou, Jing; Wu, Cheng-Ying; Zhang, Wei; Shen, Hong; Xu, Jin-Di; Zhang, Ye-Qing; Long, Fang; Li, Song-Lin
Abstract: Ethnopharmacological relevance: Poria cocos (Schw.) Wolf (Poria) is a well-known traditional medicinal fungus. It has been considered to possess spleen-invigorating ( Jianpi ) effects in traditional Chinese medicine, and is used clinically to treat spleen deficiency ( Pixu ) with symptoms of intestinal disorders such as diarrhea, indigestion, mucositis and weight loss. The aim of this study: To investigate the protective effects of Poria and its three component fractions (Water-soluble polysaccharides, WP; alkali-soluble polysaccharides, AP; triterpene acids, TA) on cisplatin-induced intestinal injury and explore the underlying mechanisms. Materials and methods: C57BL/6 mice were treated with Poria powder (PP), WP, AP and TA by oral gavage respectively for 13 days, and intraperitoneally injected with 10 mg/kg of cisplatin on day 10 to conduct a cisplatin-induced intestinal injury model. Pathological changes of ileum and colon were examined using H&E staining. The composition of gut microbiota and the alteration of host metabolites were characterized by 16S rDNA amplicon sequencing and UPLC-QTOF-MS/MS based untargeted metabolomics analysis. Results: PP and WP attenuated the cisplatin-induced ileum and colon injury, and WP alleviated the weight loss and reversed the elevation of IL-2, IL-6 in serum. Both PP and WP could mitigate cisplatin-induced dysbiosis of gut microbiota, in particular PP and WP decreased the abundance of pathogenic bacteria including Proteobacteria, Cyanobacteria, Ruminococcaceae and Helicobacteraceae, while WP promoted the abundance of probiotics, such as Erysipelotrichaceae and Prevotellaceae . Moreover, WP attenuated the cisplatin-induced alteration of metabolic profiles. The levels of potential biomarkers, including xanthine, L-tyrosine, uridine, hypoxanthine, butyrylcarnitine, lysoPC (18:0), linoleic acid, ( R )-3-hydroxybutyric acid, D-ribose, thiamine monophosphate, indolelactic acid and plamitic acid, showed significant correlations with intestinal flora. Conclusions: PP and WP possess protective effects against cisplatin-induced intestinal injury via potentially regulating the gut microbiota and metabolic profiles. Graphical abstract: Image 1